Risk and Risk-Handling Strategies in Construction Projects - Manpreet Kaur; Dr. Rajwinder Singh, (International Journal of Management Studies (IJMS), 2021)
Risk in construction projects is an object of attention due to factors namely, time, cost overruns and quality associated with construction projects. Managing those risks in construction projects is necessary in order to achieve the project objectives in terms of time, cost, quality, safety and environmental sustainability. Project risk management includes the process of risk identification, analysis, and risk-handling strategies (risk-response). Risk response strategy refers to identifying, evaluating, selecting, and implementing effective actions in order to reduce the likelihood of occurrence of risk events and/or lower the negative impact of those risks. The study aims to develop the hypothesis on selection of risk -handling strategy with specific risk situation. So, based on previous literature, the hypothesis are developed which described the relationship among the project characteristics, managers attitude towards risk and degree of controllability of risk event with choice of risk response strategy.